Adjustment of medical standards in disaster, crises and war: a scoping review of the literature - Patrick Meybohm; Stephanie Weibel; Thomas Erik Wurmb; Janno Schade; Stephanie-Julia Schräder; Maximilian Kippnich (BMJ Publishing Group, 2024)
Introduction Currently, there is a lack of evidence on how societies and healthcare systems cope with disrupting situations like disasters, crisis and wars. The aim of the scoping review was to map evidence to the following questions: Is the fact of possible overwhelming of healthcare systems accepted or denied? Are medical standards adjusted? Are dedicated contingency concepts applied? Are there triage concepts for allocating scarce resources?Methods We conducted and reported the scoping review in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for scoping reviews. A review protocol was published a priori in the Open Science Framework. Medline via PubMed was used as data source. We considered reviews, systematic reviews, guidelines and case-control studies in English or German as eligible for this scoping review, regardless of publication year or publication status. We searched Medline via PubMed up to 8 March 2023, and updated on 20 July 2023. Title/Abstract screening, full-text screening and data extraction were performed in a dual-reviewer mode.Results A total of 2213 publications were identified and 71 publications were finally included. Of these, 87% generally accepted the possibility that the capacity of the healthcare system would be overwhelmed. A structured change of medical standards was reported in 89%. 51% deployed the crisis standard of care concept. International accepted guidelines for maintaining medical care do not exist. There is no common understanding of the medical care status with regard to the standards. There is a lack of political, legal and ethical agreement on the subject of triage.Conclusion Future research must clarify which concepts and measures are suitable for building a robust healthcare system in order to maintain medical care according to accepted standards for as long as possible. Algorithms for the allocation of scarce resources must be defined in advance to enable medical staff to act with legal certainty in a crisis.